Ancient correspondence (PRO ;)
Correspondence of kings, bishops, Popes, knights, noblemen, royal servants, and Lord Chancellors covering the reigns of King John to King Henry VIII. Relates to such topics as diplomatic relations between Britain and France, political struggles between king and barons, ecclesiastical elections, the seiging of castles, etc.